2016
DOI: 10.2174/1874325001610010690
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus Induced Cartilaginous Damage and Non-linear Gross Anatomical Progression of Early-stage Osteoarthritis in a Canine Model

Abstract: Background:The predictable outcome of the anterior cruciate ligament transection (ACLT) canine model, and the similarity to naturally occurring osteoarthritis (OA) in humans, provide a translatable method for studying OA. Still, evidence of direct meniscus-induced cartilaginous damage has not been identified, and gross-anatomical blinded scoring of early-stage OA has not been performed.Objective:A gross anatomical observation and statistical analysis of OA progression to determine meniscus induced cartilaginou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…In particular, the patellar apex consistently showed the highest OAS value among the 15 sites from the preoperative period to 36 months postoperatively. Kahn et al reported that dogs euthanized 3 weeks after CrCL resection had developed damage of the femur and tibial cartilage that contacted the caudal horn of the MM, and osteophytosis at the patellar apex [ 21 ]. Additionally, osteophytosis at the cranial aspect of the stifle joint, such as osteophytosis at the patella and femoral trochlea, reportedly limits the extension of the stifle after TPLO [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the patellar apex consistently showed the highest OAS value among the 15 sites from the preoperative period to 36 months postoperatively. Kahn et al reported that dogs euthanized 3 weeks after CrCL resection had developed damage of the femur and tibial cartilage that contacted the caudal horn of the MM, and osteophytosis at the patellar apex [ 21 ]. Additionally, osteophytosis at the cranial aspect of the stifle joint, such as osteophytosis at the patella and femoral trochlea, reportedly limits the extension of the stifle after TPLO [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated the involvement of meniscal pathology in OA development and its contribution to global joint disease [20]. Meniscus induced cartilaginous damage has also been shown to result in anatomical progression of early-stage OA in a canine model [43] emphasising the importance of meniscal pathobiology in global knee joint integrity [3]. Furthermore, targeted mutation of NOV/CCN3 in mice disrupts joint homeostasis and can induce OA-like symptoms [44].…”
Section: Studies On Meniscal Tissues In Health and Diseasementioning
confidence: 99%
“…These studies are insightful as to different forms of OA which develop following meniscal or ligament injury [66]. The use of animal meniscal models [43,67,68,69,70] have also contributed significantly to a greater understanding of the pathobiology of meniscal degeneration and traumatic meniscal injury and may aid in the formulation of therapeutic interventions on these meniscal tissues [71,72].…”
Section: Studies On Meniscal Tissues In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…These canine joints belonged to a multidisciplinary study of the OA progression in our lab, which were approved by the Canadian Council on Animal Care (CCAC). Recently, a blind study of the gross anatomic disease progression in these canine joints has been completed (26). Using the OARSI scores of 0-4 that graded different parts of a joint (27), the 12-week contralateral tibias had a score of 1, while the 12-week transected tibias (OA) had a score of 2; the difference was statistical significant.…”
Section: Sample and Proceduresmentioning
confidence: 99%